First record of multi-species synchronous coral spawning from Malaysia - Chelliah, Alvin (2015)
Knowledge about the timing and synchrony of coral spawning has important implications for both the ecology and management of coral reef ecosystems. Data on the timing of spawning and extent of synchrony, however, are still lacking for many coral reefs, particularly from equatorial regions and from locations within the coral triangle. Here we present the first documentation of a multi-species coral spawning event from reefs around Pulau Tioman, Peninsular Malaysia, a popular diving and tourist destination located on the edge of the coral triangle. At least 8 coral species from 3 genera (Acropora, Montipora and Porites) participated in multi-species spawning over five nights in April 2014, between two nights before and two nights after the full moon. In addition, two Acropora species were witnessed spawning one night prior to the full moon in October 2014. While two of the Acropora species that reproduced in April (A. millepora and A. nasuta) exhibited highly synchronous spawning (100% of sampled colonies), two other common species (A. hyacinthus and A. digitifera) did not contain visible eggs in the majority of colonies sampled (i.e., <15% of colonies) in either April or October, suggesting that these species spawn at other times of the year. To the best of our knowledge, this is the first detailed documented observation of multi-species coral spawning from reefs in Malaysia. These data provide further support for the contention that this phenomenon is a feature of all speciose coral assemblages, including equatorial reefs. More research is needed, however, to determine the seasonal cycles and extent of spawning synchrony on these reefs and elsewhere in Malaysia.